Hak Tanggungan dalam Perjanjian Mudharabah - Erfandhiarta, Mohammad Pradhipta (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Mudharabah is one of the sharia banking products that in the implementation of its contract, it is mandatory to apply the principle of prudence as mandated by the Law. One form of implementation of the principle of prudence is the application of the 5C provisions which contain elements of collateral or guarantees. This study aims to analyze the validity of the guarantee for the mudharabah contract, because in principle the mudharabah contract is a trust contract that does not require collateral. The study uses a normative legal research method to determine the concept of collateral in mudharabah according to Islamic law, especially regarding the position of Mortgage Rights on the mudharabah contract in terms of Islamic Law and Positive Law.